THE VISCERA (International journal of artificial intelligence, 2025)
The viscera refer to the internal organs located within the main cavities of the body, especially those within the thoracic and abdominal cavities. These include vital organs such as the heart, lungs, liver, stomach, intestines, kidneys, and pancreas. Each visceral organ performs specific physiological functions essential for maintaining homeostasis, metabolism, and overall body health. Disorders of the viscera can lead to serious diseases affecting the cardiovascular, respiratory, digestive, and urinary systems. Understanding the structure, function, and care of these organs is essential for promoting health and preventing internal organ diseases.